Validation and application of breakage model in the discrete element method through the simulation of comminution systems - André, Flávio Pereira (2019)
The present work describes a detailed empirical-phenomenological model that characterizes all relevant aspects of body breakage and has been implemented in the commercial DEM platform Rocky DEM, adopting a particle replacement scheme to represent particle fragmentation. The model describes fundamental properties of ore particles, such as the distribution of fracture energy among a population of particles, the size effect on breakage probability, the weakening of particles due to repeated stressing events and the relation between energy and fragment size distribution. At a first stage, the verification of the model has been carried out by comparing results from the analytical model previously fitted to experimental data with simulations of single particle breakage tests. Sensitivity analysis of simulations varying different relevant parameters has also been performed. Afterwards, the simulation model was validated by comparing its results to drop ball test experiments on unconfined particle beds. The good agreement demonstrates the potential of the model to simulate more complex systems in which DEM simulations must include an effective description of breakage. Finally, the model has been used to simulate a laboratory-scale cone crusher and a pilot-scale horizontal shaft impact crusher.